Conflict Resolution Based on Malay "Tunjuk Ajar" (Traditional Guidance) in Addressing Community Conflicts Among the Malay People in Riau Province - Ryan Prayogi; Kokom Komalasari; Rahmat; Iim Siti Masyitoh; Bunyamin Maftuh; Elly Malihah; Ryan Prayogi (ASANKA : Journal of Social Science and Education, 2026)
This study contributes theoretically to conflict resolution and Civic Education by demonstrating how local wisdom can operationalize deliberative democracy principles in multicultural settings. Employing a qualitative descriptive design with 15 purposively selected participants, the research explores conflict resolution based on the Malay "Tunjuk Ajar" among the Malay people in Riau Province. Data were collected through observation, in-depth interviews, and literature review. The principal findings reveal that conflict resolution is operationalized through "duduk berundiang" to achieve consensus, facilitated by the Riau Malay Customary Institution. The process predominantly employs integrating, compromising, and obliging conflict management styles, embodying the core values of deliberation, consensus, truth, justice, responsibility, and social concern. The novelty lies in its explicit integration of Malay Tunjuk Ajar with Civic Education frameworks, linking customary deliberation to Pancasila's democratic principles and to the development of civic competence. Practically, this study provides a culturally grounded model for conflict resolution that can complement formal legal mechanisms and inform Civic Education curricula on multicultural citizenship.